Kurikulum 2013 Pengembangan SIT dan Kurikulum Khas di SMPIT Al Uswah Bangil - Syarifah; Ahmad Saifulloh; Saiful Anwar; Rakhmatusakdiyah; Nur Firdaw Buerahen (State Islamic Institute of Madura, 2024)
This study aims to find out how the development of the Curriculum 2013 SIT (Integrated Islamic School), and the typical 8th grade curriculum at SMPIT Al Uswah Bangil. This research is qualitative descriptive field research, the data collection techniques used are interviews, observations, and documentation using Miles and Huberman data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results showed that curriculum development at SMPIT Al Uswah Bangil was developed in all school curricular activities, namely intracurricular, co-curricular and extracurricular activities. SMPIT Al Uswah Bangil also uses the concept of Islamization of science, and the implementation of evaluation is carried out in the form of curriculum supervision techniques.